2020
DOI: 10.1158/1940-6207.capr-19-0474
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Risk Factors in a Comparison of a Barrett Esophagus Registry (BarrettNET) and a Case–Control Population in Germany

Abstract: Endoscopic screening for Barrett's esophagus as the major precursor lesion for esophageal adenocarcinoma is mostly offered to patients with symptoms of gastroesophageal reflux disease (GERD). However, other epidemiologic risk factors might affect the development of Barrett's esophagus and esophageal adenocarcinoma. Therefore, efforts to improve the efficiency of screening to find the Barrett's esophagus population "at risk" compared with the normal population are needed. In a cross-sectional analysis, we compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
7
0
3
Order By: Relevance
“…However, only a fraction of patients with BO develop oesophageal adenocarcinoma, which raises important economic and clinical questions about whom to screen. [10] Numerous studies have been conducted in order to assess the correlation between symptoms of gastro-oesophageal reflux, or GORD, and the presence of BO, in an attempt to inform decisions regarding how to optimise endoscopic follow-up of their patients, in order to provide early diagnosis, detect any other complications, and reduce the associated management costs. Systematic analysis of studies that report these types of data is important, in order to provide physicians with more precise estimates of the prevalence of BO in patients with symptoms of gastro-oesophageal reflux, or GORD, in order to inform clinical practice, as well as to identify areas where further research is needed.…”
Section: What Are the New Findings?mentioning
confidence: 99%
“…However, only a fraction of patients with BO develop oesophageal adenocarcinoma, which raises important economic and clinical questions about whom to screen. [10] Numerous studies have been conducted in order to assess the correlation between symptoms of gastro-oesophageal reflux, or GORD, and the presence of BO, in an attempt to inform decisions regarding how to optimise endoscopic follow-up of their patients, in order to provide early diagnosis, detect any other complications, and reduce the associated management costs. Systematic analysis of studies that report these types of data is important, in order to provide physicians with more precise estimates of the prevalence of BO in patients with symptoms of gastro-oesophageal reflux, or GORD, in order to inform clinical practice, as well as to identify areas where further research is needed.…”
Section: What Are the New Findings?mentioning
confidence: 99%
“…In addition, genomic analysis by restriction fragment length polymorphism indicated that the highest frequencies of Y-chromosomal haplogroups are associated with BE and EAC in White males ( Westra et al., 2020 ). Recent case–control studies demonstrate that gastroesophageal reflux disease in male patients is highly associated with the development of BE in Germany ( Schmidt et al., 2020 ). These reports supported the present results, indicating that predicted dark gray modules with the highest association with gender must have a clinically significant module.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal experiment simulating BA reflux, overexpression of the inflammatory cells, IL-6 and TNF- α, was found [ 62 ]. This indicated that gut bacterial alterations could indirectly induce the esophageal mucosal inflammation and carcinogenesis [ 62 , 63 , 64 ]. Despite a wealth of data on the role of gut bacteria in GI tract disease, we have only recently recognized the association of gut viruses with some GI tract diseases, including CRC in which the diversity of the gut viruses is significantly increased in stool samples from CRC patients, suggesting a disease-specific signature that can be used to differentiate CRC samples from controls [ 37 ].…”
Section: Discussionmentioning
confidence: 99%